2007
DOI: 10.1111/j.1365-2435.2007.01289.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution on ecological time‐scales

Abstract: Summary1. Ecologically significant evolutionary change, occurring over tens of generations or fewer, is now widely documented in nature. These findings counter the long-standing assumption that ecological and evolutionary processes occur on different time-scales, and thus that the study of ecological processes can safely assume evolutionary stasis. Recognition that substantial evolution occurs on ecological time-scales dissolves this dichotomy and provides new opportunities for integrative approaches to pressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
487
1
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 577 publications
(509 citation statements)
references
References 82 publications
9
487
1
12
Order By: Relevance
“…Widespread occurrence of the PRM mechanism would easily explain recently reported cases of apparent phenotypic evolution over ecological time (Reznick and Ghalambor, 2001;Hairston et al, 2005;Carroll et al, 2007;Schoener, 2011). In most such cases, there has been no genetic evidence demonstrating the operation of the classic Neo-Darwinian mechanism of allelic replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Widespread occurrence of the PRM mechanism would easily explain recently reported cases of apparent phenotypic evolution over ecological time (Reznick and Ghalambor, 2001;Hairston et al, 2005;Carroll et al, 2007;Schoener, 2011). In most such cases, there has been no genetic evidence demonstrating the operation of the classic Neo-Darwinian mechanism of allelic replacement.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that evolution can occur on an ecological time-scale (see [5,23,24] for examples). Thus, ER could, in theory, be an important mechanism by which wild species can adapt to human-induced changes [25,26].…”
Section: Evidence For Evolutionary Rescue In Vertebratesmentioning
confidence: 99%
“…S pecies interactions are a source of selective pressures that can maintain genetic variability in host populations, parasitism being a classic example [1][2][3] . In particular, this is true for the major histocompatibility complex (MHC) in vertebrates.…”
mentioning
confidence: 99%